Adults social media addiction and phubbing latent profiles and authenticity as outcome - Ali Kirksekiz; Mehmet Yildiz; Mübin Kiyici; Mürüvvet Emrem; Sevgi Koroglu; Metin Yıldız (BMC Psychology)
Abstract This study was conducted to examine the effect of social media addiction and phubbing on authenticity in adults. This study based on person-centered approach and cross-sectional design, was conducted with 1046 individuals living in Turkiye between February and August 2024. R programming language 4.1.3, G*Power 3.1 and SPSS-22 program were used in the analysis of the study. With LPA it was found that there are 3 classes. It was found that individuals with high digital addiction had low levels of authenticity (p <.05). In our study, digital addiction was found to negatively affect the level of authenticity. It is recommended to examine the effect of digital addiction on autism and other psychological factors.